PENGARUH PENGUMUMAN MERGER DAN AKUISISI TERHADAP RETURN SAHAM PERUSAHAAN AKUISITOR DAN NON AKUISITOR DALAM SEKTOR INDUSTRI YANG SAMA DI BURSA EFEK JAKARTA - Amin Wibowo; Yulita Milla Pakereng (Faculty of Economics and Business, Universitas Gadjah Mada, 2001)
The purposes of this research are: (1) to examine the information content of merger and acquisition announcement in acquiring and nonacquiring firm in the same industrial sector and (2) to determine whether there is information transfer in the same industrial sector.Using sample firms of manufacturing industry listed in Jakarta Stock Exchange and research period of 1991-1997, the result shows that, in general, there is information content in merger and acquisition announcement for acquiring and nonacquiring firms. The study also indicates that there is information transfer between firms in the manufacturing industry for merger and acquisition announcement case. Another findings is that there is information leakage, i.e. the public knows information about merger and acquisition prior to the announcement.